Palinología de la Formación Monte Chico (Cretácico tardío) de la provincia de Santa Cruz, Argentina: granos de polen de gimnospermas - Povilauskas, Leticia Karina (2012)
Palynological assemblages composed by continental and marine palynomorphs were recovered from the Monte Chico Formation, late Cretaceous, Santa Cruz Province. In this contribution palynological assemblages shaped by pollen grains belonging to the gymnosperms were studied. The samples were taken from the all section of this unit. Sixteen species of pollen grains were here determined. They belong to the genera: Araucariacites, Classopollis, Cycadopites, Dacrycarpites, Gamerroites, Lygistepollenites, Microcachyridites, Phyllocladidites, Podocarpidites and Trisaccites. On the basis of the stratigraphic distribution of the identified species, mainly in Argentina and Antarctica, and joined with the preliminary analysis determinate of spores, a Maastrichtian-Late Maastrichtian age is here suggested. The palynological assemblages obtained would indicate a typically marine near of shore environment of deposition, with continental conditions towards to the upper section.